Effects of exercise and psychological interventions on smartphone addiction among university students: A systematic review - Liu, Huange; Soh, Kim Geok; Samsudin, Shamsulariffin; Rattanakoses, Watnawat; Qi, Fengmeng (Frontiers in Psychology, 2022)
Background and aims: Among the large number of studies on smartphone addiction, only a few randomized controlled trials on exercise and psychological interventions for smartphone addiction by university students have been published. This study aims to systematically investigate the impact of exercise and psycho-logical interventions on smartphone addiction among university students. Methods: The PRISMA guidelines were adopted for this systematic literature review. Prominent academic databases such as Web of Science, PubMed, ProQuest, Cochrane Library, China National Knowledge Infra-structure (CNKI) and PsycINFO were searched to find eligible studies published before Aug 2021. The overall quality of the articles was checked using the “QualSyst” tool by Kmet et al. Results: From among 600 papers, 23 met the inclusion criteria and were incorporated into our systematic re-view. All of the studies were randomized controlled trials. The following thematic areas emerged as a result of the content analysis: study selection and design, as well as study characteristics (participants, intervention, comparisons, and outcomes). Discussion and conclusion: The literature on exercise and psychological interventions for smartphone addiction is scarce. There is a need to introduce new interventions and to validate the effectiveness of combined interventions. Our findings suggest that exercise and psychological interventions may help to reduce smartphone addiction. This combination was more effective compare to exercise or psychological intervention on mental health and addiction among university students. Future research should combine exercise and psychological interventions, focusing on university students, especially females, who are vulnerable to smartphone addiction.Further studies should focus on the cross-section of neuropsychology, cognitive psychology, and sports science to provide combined interventions in physiological and psychological direction.